2006
DOI: 10.1063/1.2212058
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the enhanced performance in poly(3-hexylthiophene): [6,6]-phenyl C61-butyric acid methyl ester solar cells upon slow drying of the active layer

Abstract: The origin of the enhanced performance of bulk heterojunction solar cells based on slowly dried films of poly(3-hexylthiophene) (P3HT) and [6,6]-phenyl C61-butyric acid methyl ester is investigated, combining charge transport measurements with numerical device simulations. Slow drying leads to a 33-fold enhancement of the hole mobility up to 5.0×10−7m2V−1s−1 in the P3HT phase of the blend, thereby balancing the transport of electrons and holes in the blend. The resulting reduction of space-charge accumulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
159
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(171 citation statements)
references
References 21 publications
8
159
0
4
Order By: Relevance
“…Two of the four contacts used here in the tandem configuration are known to be efficient in BHJ solar cells, namely, 140 nm ITO/ 50 nm PEDOT:PSS as anode for the bottom cell and 1 nm LiF / 80 nm Al as cathode of the top cell. [18][19][20][21][22][23] Now, the semitransparent cathode of the bottom cell and the semitransparent anode of the top cell have to be defined. The requirements for these electrodes are: as thin as possible to obtain maximum transparency, conductive enough to extract charge carriers, and stable during spin coating of the PTrFE optical spacer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the four contacts used here in the tandem configuration are known to be efficient in BHJ solar cells, namely, 140 nm ITO/ 50 nm PEDOT:PSS as anode for the bottom cell and 1 nm LiF / 80 nm Al as cathode of the top cell. [18][19][20][21][22][23] Now, the semitransparent cathode of the bottom cell and the semitransparent anode of the top cell have to be defined. The requirements for these electrodes are: as thin as possible to obtain maximum transparency, conductive enough to extract charge carriers, and stable during spin coating of the PTrFE optical spacer.…”
Section: Resultsmentioning
confidence: 99%
“…If, for example, a thickness of 300 nm is required for optical out coupling, the occurrence of unbalanced transport may lead to the formation of space charges, giving rise to a reduced fill factor ͑FF͒ and performance. [19][20][21][22][23] In order to improve the first generation solution-processed tandem cells, we introduce here an additional solution-processable, transparent, and insulating layer which serves as an optical spacer and leads to the fabrication of a four-contact tandem cell ͓Fig. 1͑b͔͒.…”
Section: Introductionmentioning
confidence: 99%
“…(Hoppea & Sariciftci, 2004;Padinger et al, 2003) Other methods used in the past to control the morphology of BHSC involve the use of appropriate solvents with specific boiling point that allow either the increase or decrease of the solvent evaporation rate. Shaheen et al, 2001;Yu et al, 1995) Other methods, such as reducing the drying speed of spin-coated films, (Li et al, 2005;Mihailetchi et al, 2006;Vanlaeke et al, 2006) solubility matching (Troshin et al, 2009) and the melting of bilayers have also been used. (Kim, Liu & Carroll, 2006) It was observed that chemical additives can substitute the post production treatment of BHSC.…”
Section: Methods To Control the Morphology Of Bhscmentioning
confidence: 99%
“…Protocols for controlling the formation of morphology with self-organized ordered structures of the polymer units within the active layer can be realized by appropriate solvent selection [63], slow drying of spin-coated films [64][65][66], thermal [67][68][69] and solvent annealing [70][71][72] treatment of the films, surface treatment of ITO [73], the application of an electric field [74], the use of chemical additives [75], additive-spraying techniques [76], and the use of nanowires (NWs) [77] and nanoparticles [78].…”
Section: Strategies For Controlling the Active-layer Morphology In Bhjsmentioning
confidence: 99%